“THINGS I CANNOT CHANGE”: Moral Distress in the Implementation of Ontario Works - Baker Collins, Stephanie; Cranmer-Byng, Sheila (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2018)
Moral distress is an important topic, particularly given the impact of unacknowledged moral distress on professional practice, including social work. Interviews with Ontario Works (OW) case managers working in regional offices in southern Ontario form the backdrop of an analysis of moral distress in the context of a highly rule-bound environment combined with unmet needs. This study focuses particularly on the role of structural constraints, such as policy restrictions as contributors to moral distress. The concept of moral distress is complicated by noting that distress is not always in response to a desire to act in the best interest of the client. An argument is developed that situating moral distress in a discussion of professional and feminist ethics encourages a deeper analysis of the implications of moral distress for professionals working in restrictive policy environments.